Towards Digital Segregation? Problematizing the Haves and Have Nots in the Smart City - Foley, Rider W.; Nadjari, Sam; Eshirow, John; Adekunle, Rahman; Codjoe, Paul (Frontiers in Sustainable Cities, 2022)
Scholars, policymakers, and issue advocates have long pointed to the digital divide and systemic injustices that pervade designs for the smart city. For many this debate centers around the ‘haves’ and ‘have nots’ and the differences between those social groups. This research problematizes that binary classification and articulates a more nuanced set of social groups. Evidence from surveys and participant observations suggest that the smart city is further segregating urban residents along socio-economic lines. While some users will reap financial and social rewards from digital commerce, recreation and social life, others will be preyed upon, victimized or excluded. This will privilege a small group of elites and allow them to perpetuate digital segregation in the smart city. We close we a discussion on how to create pathways for greater inclusion and community-based governance.